Studying the Environmental Changes Using Remote Sensing and GIS - Yousef, Ola Abdul Razzaq; Jaber , Hussein Sabah (Iraqi Journal of Science, 2023)
The research aims to monitor environmental changes and study the state of desertification in the northeastern part of the Al-Najaf province, Iraq. The study area suffers from desertification and drought phenomena. Remote sensing systems "RS" and geographic information systems "GIS" are essential for monitoring environmental changes because they provide Earth observation satellites that contribute to detecting environmental changes. Two Sentinel 2 images were acquired on December 26, 2015, and November 29, 2021. The images were combined and used for indices calculations. Normalized vegetation difference index "NDVI,” Normalized difference index "NDWI," soil exposure index "BSI," and Normalized difference index "NDBI." The results showed that the extent of desertification in the study area began to increase during the study period. Also, the results of change detection showed that the study area became very dry, especially in the western part, suffering from dunes, barren land, and a lack of water sources, especially in the western part of the study area.